A constituinte escolar no Rio Grande do Sul como política pública de um governo democrático popular: um estudo sobre o Instituto Estadual de Educação Professor Pedro Schneider(São Leopoldo) - Schmitz, Taís (Universidade do Vale do Rio do Sinos, 2007)
This dissertation is a process and a product of my master’s degree research in the Program of Masters degree in Education of Vale do Rio dos Sinos University – UNISINOS. The research situates itself in the field of History, Politics and Education and its theme is the Constituent of the School in Rio Grande do Sul State, a movement of the recent History, and it analyses the management of education through the sectorial politics of the administration Olívio Dutra (1999-2002). The Constituent of the School objectified the construction of the democratic and popular school in the State, which intended to break with the ruling model of education public politics whose purpose was the definition of principles and guidelines of the education for the State net of teaching. The objective of the research is to investigate the Constituent of the School in the State Institute of Education Teacher Pedro Schneider (Pedrinho) in São Leopoldo/RS as public politics in the attempt to implement the democratic school as space of f
Keywords: cidadania; gestão democrática; história; política educacional; constituinte escolar; citizenship; democratic management; educational politics; history; constituent of school; Ciências Humanas